# maths

posted by Candice

by equating the coefficients of sin x and cos x , or otherwise, find constants A and B satisfying the identity.

A(2sinx + cosx) + B(2cosx - sinx) = sinx + 8cosx

I got A = 2, B = 3, which the answers said were correct.

However, another part of the question asked

hence integrate

sinx + 8cosx
-------------dx
2sinx + cosx

and the answers were 2x + 3Ln (2sinx + cosx) + C

Could you explain how to get this?

1. Steve

use what the first part showed. Using c for cos and s for sin, you showed that

s+8c = 2(2s+c) + 3(2c-s)

so,

(s+8c)/(2s+c)
= [2(2s+c) + 3(2c-s)]/(2s+c)
= 2 + 3(2c-s)/(2s+c)

now, you have ∫2 dx + ∫3du/u
integral is

2x + 3lnu
= 2x + 3ln(2s+c) + C

## Similar Questions

1. ### Trig

prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= sinx^2 ^3 = (1-cosX^2)^3 = (1-2CosX^2 + cos^4) (1-cosX^2) then multiply that out 1-2CosX^2 + cos^4 - cosX^2 + 2cos^4 -cos^6 add that on the left to the cos^6, and …
2. ### trig

express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?
3. ### Maths

Solve this equation fo rx in the interval 0<=x<=360 3sinxtanx=8 I would do it this way: sinxtanx = 8/3 sinx(sinx/cosx)=8/3 sin^2x/cosx = 8/3 (1-cos^2x)/cosx=8/3 cross-multiply 3 - 3cos^2x = 8cosx 3cos^2x + 8cosx - 3 = 0 (3cosx-1)(cosx+3)=0 …
4. ### Trigonometry.

( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated side …
5. ### Trig.......

I need to prove that the following is true. Thanks (2tanx /1-tan^x)+(1/2cos^2x-1)= (cosx+sinx)/(cosx - sinx) and thanks ........... check your typing. I tried 30ยบ, the two sides are not equal, they differ by 1 oh , thank you Mr Reiny …
6. ### Trig........

I need to prove that the following is true. Thanks (cosx / 1-sinx ) = ( 1+sinx / cosx ) I recall this question causing all kinds of problems when I was still teaching. it requires a little "trick" L.S. =cosx/(1-sinx) multiply top and …
7. ### math

tanx+secx=2cosx (sinx/cosx)+ (1/cosx)=2cosx (sinx+1)/cosx =2cosx multiplying both sides by cosx sinx + 1 =2cos^2x sinx+1 = 2(1-sin^2x) 2sin^2x + sinx-1=0 (2sinx+1)(sinx-1)=0 x=30 x=270 but if i plug 270 back into the original equation …
8. ### Math

1) evaluate without a calculator: a)sin(3.14/4) b) cos(-3(3.14)/4) c) tan(4(3.14)/3) d) arccos(- square root of three/2) e) csctheata=2 2) verify the following identities: a) cotxcosx+sinx=cscx b)[(1+sinx)/ cosx] + [cosx/ (1+sinx)]= …
9. ### Trigonometry

How do you simplify: (1/(sin^2x-cos^2x))-(2/cosx-sinx)?
10. ### math;)

The equation 2sinx+sqrt(3)cotx=sinx is partially solved below. 2sinx+sqrt(3)cotx=sinx sinx(2sinx+sqrt(3)cotx)=sinx(sinx) 2sin^2x+sqrt(3)cosx=sin^2x sin^2x+sqrt(3)cosx=0 Which of the following steps could be included in the completed …

More Similar Questions